2014
DOI: 10.3109/13880209.2014.946059
|View full text |Cite
|
Sign up to set email alerts
|

Raspberry ketone, a naturally occurring phenolic compound, inhibits adipogenic and lipogenic gene expression in 3T3-L1 adipocytes

Abstract: Context: Raspberry ketone (RK) is a natural phenolic compound of red raspberry. The dietary intake of RK has been reported to exert anti-obese actions and alter the lipid metabolism in vivo and human studies. Objective: To elucidate a possible mechanism for anti-obese actions of RK, the effects of RK on the adipogenic and lipogenic gene expression in 3T3-L1 adipocytes were investigated. Materials and methods: 3T3-L1 maturing pre-adipocytes were treated from day 2 to day 8 of differentiation and mature adipocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Although RK is promoted as a dietary supplement, as a product to help promote or maintain weight loss, there are few studies that document a clear effect [32,33]. More recently, publications investigating aspects of raspberry ketone have evaluated bone cell differentiation [34]; fatty liver [35]; and gene expression changes [36]. The efficacy of RK is not known with certainty at this time.…”
Section: Introductionmentioning
confidence: 99%
“…Although RK is promoted as a dietary supplement, as a product to help promote or maintain weight loss, there are few studies that document a clear effect [32,33]. More recently, publications investigating aspects of raspberry ketone have evaluated bone cell differentiation [34]; fatty liver [35]; and gene expression changes [36]. The efficacy of RK is not known with certainty at this time.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the insulin sensitization induced by PPARγ is in part mediated by c/EBPα activation. On the other hand, in addition to controlling insulin action, c/EBPα is required for maintaining expression of PPARγ in the mature fat cell [27], and both are considered key regulators in fatty acid biosynthesis and accumulation [28]. On the basis of the intracellular triglyceride accumulation results, we were expecting a decrease in c/EBPα and PPARγ protein expression after the treatments with ellagic acid and urolithin A.…”
Section: Effect Of Ellagic Acid and Urolithins A And B On Transcriptimentioning
confidence: 99%
“…Experimental studies have shown that it alters lipid metabolism in adipocytes (Park 2015) and enhances noradrenaline-induced lipolysis (Morimoto and others 2005). There is limited information on the safety and toxicity of raspberry ketone in both animals and humans (Bredsdorff and others 2015).…”
mentioning
confidence: 99%